Qualificação e empregabilidade: um estudo a partir da realidade da indústria têxtil em Sergipe - Araújo, Sérgio Luiz Elias de (2008)
This research has as general objective to identify to the relation between qualification and employability for the worker of the great and average textiles industries of Aracaju and its metropolitan region, having as specifics objectives to raise the profile of these companies, to verify the demanded pertaining to school qualification for the admission of professionals of the averages and great industrial companies of the textile branch, as well as presenting suggestions that can contribute for the decrease of the index of unemployment in Sergipe. This work has the pretension also to argue the contradiction, the possibility and the reality as methodological categories and the qualification and the employability as categories of content. Here a critical analysis on the productive reorganization in Brazil and the consequences of Toyotismo for the Brazilian workers will be seen it. Also it will be argued as the precarious work and the unemployment had become in the consequences most serious of the adopted economic policies in Brazil in the last few decades. The notion of ability will be studied and will be seen that employability is the given label the union between adaptability, flexibility and creativity taken to the extremity. Finally, the results of the collected data will be presented and its had interpretations and carried through the final considerations, where the empirical and theoretical data concerning the education, of the employability , the unemployment and the precarious work will be argued, beyond being presented critical and suggestions to the system of the job and work in Brazil.